2019
DOI: 10.1111/exd.13903
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin as an opener of mitochondrial potassium channels in dermal fibroblasts

Abstract: Flavonoids belong to a large group of polyphenolic compounds that are widely present in plants. Certain flavonoids, including naringenin, have cytoprotective properties. Although the antioxidant effect has long been thought to be a crucial factor accounting for the cellular effects of flavonoids, mitochondrial channels have emerged recently as targets for cytoprotective strategies. In the present study, we characterized interactions between naringenin and the mitochondrial potassium (mitoBKCa and mitoKATP) cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
(80 reference statements)
3
18
0
Order By: Relevance
“…In our experimental model, we also examine in detail the functional role of the mitoBK Ca channel. The presented study complements the previous biochemical and functional characteristics of the mitoBK Ca channels present in fibroblast cells [30] and in vascular smooth muscle cells [31].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our experimental model, we also examine in detail the functional role of the mitoBK Ca channel. The presented study complements the previous biochemical and functional characteristics of the mitoBK Ca channels present in fibroblast cells [30] and in vascular smooth muscle cells [31].…”
Section: Introductionsupporting
confidence: 82%
“…In our previous study, we observed a similar interaction of naringenin with the mitoBK Ca channel identified in the mitochondria of human skin fibroblasts [30]. However, the stimulatory effects of naringenin on the mitoBK Ca channel in skin fibroblasts were stronger than those observed in endothelial cells.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, the cardioprotective function of naringenin due to activation of the cardiac mitoBK Ca channel was shown [114]. Additionally, with the use of patch-clamp single channel measurements, it was shown in skin fibroblasts that both the mitoK ATP and mitoBK Ca channels were activated by naringenin [111]. These studies suggest that naringenin may function as a potassium channel opener towards mitochondrial potassium channels in skin-derived cells.…”
Section: Cgs7184mentioning
confidence: 96%
“…Drug repositioning involves the investigation of existing drugs for new therapeutic applications. Recently, a new set of mitochondrial potassium channels was discovered in skin-derived cells: keratinocytes, dermal fibroblasts, and endothelial cells [25,35,40,53,111]. Naringenin, a plant-derived flavonoid, has been known for many years to have the potential to improve many health problems, such as cardiovascular, metabolic, neurological, and pulmonary disorders; and cancer [112,113].…”
Section: Cgs7184mentioning
confidence: 99%
“…The naringenin-induced effects observed in this study were again antagonized by paxilline. In 2019, Kampa et al finally showed the direct interaction of the flavonoid naringenin with mitochondrial potassium channels [203]. It has been demonstrated using isolated mitoplasts from primary human dermal fibroblasts and patch-clamp that naringenin at micromolar concentrations directly increases mitoBK Ca and mitoK ATP channel activity.…”
Section: Mitochondrial Ion Channel Openersmentioning
confidence: 99%